Over Here : the First World War and American Society. - Kennedy, David M. (Oxford University Press, Incorporated, 2004)
This 25th anniversary edition includes a new afterword from Pulitzer Prize-winning author David M. Kennedy, that explains his reasons for writing the original edition as well as his opinions on the legacy of Wilsonian idealism, most recently reflected in President George W. Bush's national security strategy. More than a chronicle of the war years, Over Here uses the record of America's experience in the Great War as a prism through which to view early twentieth century American society.